Experiences of Violence Among Transgender Women in Puerto Rico: An Underestimated Problem. Issue 2 (28th January 2017) - Rodríguez-Madera, Sheilla L.; Padilla, Mark; Varas-Díaz, Nelson; Neilands, Torsten; Vasques Guzzi, Ana C.; Florenciani, Ericka J.; Ramos-Pibernus, Alíxida
ABSTRACT: Violence is a public health concern faced on a daily basis by transgender women. Literature has documented how it adversely affects quality of life and health and in some instances leads to homicide. Considering the lack of research documenting the experiences of violence among transgender women, the objective of this article was to explore manifestations of violence among this population in Puerto Rico. The data presented in this article are part of a larger study on transgender/transsexual health in Puerto Rico. For the purpose of this article we focus on the quantitative data analysis. Participants ( N  = 59 transgender women) were recruited via respondent driven sampling. Implications and specific recommendations are discussed in light of these findings.